An appetite for wonder : the making of a scientist : a memoir - Dawkins, Richard, 1941- (London : Bantam Press, 2013)
Born to parents who were enthusiastic naturalists, and linked through his wider family to accomplished scientists, Richard Dawkins was bound to have biology in his genes. But what were the influences that shaped his life and intellectual development? And who inspired him to become the pioneering scientist and thinker now famous around the world? --
BIBINDX
Keywords: Dawkins, Richard, -- 1941- -- Childhood and youth; Scientists -- Biography -- Great Britain; Ethologists -- Great Britain -- Biography; Zoologists -- Great Britain -- Biography